Responses of Withania frutescens (L.) Pauquy (Solanaceae) Growing in the Mediterranean Area to Changes in the Environmental Conditions: An Approach of Adaptation - Moussaoui, Abdelfattah El; Bourhia, Mohammed; Jawhari, Fatima Zahra; Khalis, Hind; Chedadi, Mohamed; Agour, Abdelkrim; Salamatullah, Ahmad Mohammad; Alzahrani, Abdulhakeem; Alyahya, Heba Khalil; Alotaibi, Asdaf; Bousta, Dalila; Bari, Amina (Frontiers in Ecology and Evolution, 2021)
Background: Plant growth is frequently influenced by the environmental conditions that affect the plant. The objective of the study: The present research work was undertaken to study the response of Withania frutescens to changes in the environmental conditions by investigating topographical, climatological, morphological, histological, and phytochemical aspects that influencing plant growth. Material and Methods: The topography of the study area was described using the Digital Terrain Model (DTM). The bioclimatic study was carried out using a climatological database (TerraClimate) recorded for the periods 1960-1970 as an old period (AP) and 2000-2019 as a new period (NP). The histological study on stems, leaves, and roots was investigated according to protocols as described in the present study. The phytochemical analysis was assessed using gas chromatograph coupled to a mass spectrophotometer after silylation. Results: The topographical study showed that the selected stations were varied in terms of topographical characteristics. The average annual precipitation recorded for the study area is 624 mm/year, and the thermal amplitude is about 34.64°C. The Morphometry study revealed that the plant had changes in length and width from one zone to another. The histometrical study of organs showed also changes in tissue structure over time and space. The phytochemical content in the studied plants was found to be also vary over time and space. Conclusion. Based on the obtained results, we could confirm that W. frutescens has developed different strategies to mitigate hard environmental conditions.